2018
DOI: 10.2147/cmar.s181922
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in DNA repair pathway genes and&nbsp;<em>ABCG2</em>&nbsp;gene in advanced colorectal cancer: correlation with tumor characteristics and clinical outcome in oxaliplatin-based chemotherapy

Abstract: ObjectiveMultiple factors are involved in oxaliplatin-resistant process in colorectal cancer (CRC) patients including decreased drug accumulation and enhanced capacity to repair and tolerate DNA damage. In the present study, we aimed to assess the impact of six single-nucleotide polymorphisms (SNPs) in DNA repair genes and ABCG2 gene on prognosis in advanced CRC patients treated with oxaliplatin-based chemotherapy.MethodsIn this study, 580 advanced CRC patients were recruited. Six SNPs of DNA repair genes (XPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The previous study reported that FBXW4 regulates the ubiquitination and cell cycle (Lockwood et al, 2013). In the present study, we found that FBXW4 was not only related to the cell cycle signaling pathway, but was also related to the DNA replication signaling pathway, which is associated with oxaliplatin resistance (Martinez-Balibrea et al, 2015;Hu et al, 2019). However, the underlying mechanism by which FBXW4 increases FOLFOX regimen sensitivity in mCRC patients is still unclear.…”
Section: Discussionmentioning
confidence: 51%
“…The previous study reported that FBXW4 regulates the ubiquitination and cell cycle (Lockwood et al, 2013). In the present study, we found that FBXW4 was not only related to the cell cycle signaling pathway, but was also related to the DNA replication signaling pathway, which is associated with oxaliplatin resistance (Martinez-Balibrea et al, 2015;Hu et al, 2019). However, the underlying mechanism by which FBXW4 increases FOLFOX regimen sensitivity in mCRC patients is still unclear.…”
Section: Discussionmentioning
confidence: 51%
“…In Table S3 ( Supplementary Material ), three SNPs in the XPC gene that are potentially predictive of treatment response to oxaliplatin-based therapy in CRC patients are reported ( Liu et al., 2012 ; Kap et al., 2015 ; Hu et al., 2019 ). Only one SNP was significantly associated with survival.…”
Section: Resultsmentioning
confidence: 99%
“…Following our selection criteria, for XPA in the NER pathway ( Stoehlmacher et al., 2004 ; Monzo et al., 2007 ; Hu et al., 2019 ), SRBC in the HR pathway ( Moutinho et al., 2014 ) and MGMT in the DNA synthesis pathway ( Park et al., 2010 ) results remain inconclusive because the observed associations have not yet been replicated and the studies itself were relatively small (<300 patients).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to A23G SNP, the G709A SNP has virtually no impact on the repair of UV-and benzo(a)pyrene diol epoxide-induced DNA damage compared to wild-type XPA [186,187], and appears to have a protective effect for LC patients [166][167][168]. [154,155,159,[166][167][168][169][170][171][172][173][174][175][176][177][178][179][180]185,[191][192][193] Three further SNPs reside in intron sequences of XPA: rs3176658, which causes C to T transition, rs3176721, a C to A transversion, and rs2808667, a T to C transition (www.ncbi.nlm.nih.gov/snp). rs3176658 and rs3176721 are associated with efficacy of platinum-based chemotherapy in LC [188], while rs3176658 alone has been shown to be significantly associated with LC risk [189] and with response to neoadjuvant radiochemotherapy treatment of locally advanced rectal cancer (RC) [190].…”
Section: Xpa Polymorphisms and Cancer Incidence And Treatment Outcomementioning
confidence: 93%
“…These SNPs are located at transcription factor binding sites, impacting XPA mRNA level, which may influence the cellular response to platinum-based chemotherapies. Indeed, rs10817938 heterozygous CT and homozygous TT genotypes have been associated with longer overall survival (OS) in colorectal cancer (CRC) patients receiving oxaliplatin-based chemotherapy [155]. In addition, these SNPs have been shown to be associated with the risk and development of numerous cancers and display significant gene-environment interactions (see below).…”
Section: Xpa Polymorphisms and Cancer Incidence And Treatment Outcomementioning
confidence: 99%